Glycemic control during TB treatment among Filipinos: The Starting Anti-Tuberculosis Treatment Cohort Study. - Lauren Oliveira Hashiguchi; Julius Patrick Ferrer; Shuichi Suzuki; Benjamin N Faguer; Juan Antonio Solon; Mary Christine Castro; Koya Ariyoshi; Sharon E Cox; Tansy Edwards (Public Library of Science (PLoS), 2024)
Poor TB treatment outcomes are observed in patients with type 2 diabetes mellitus (DM) comorbidity and glycemic control throughout treatment may play a role. The objective of this study was to investigate glycemic control longitudinally among Filipino adults undergoing TB treatment using mixed-effects linear and logistic regression. Analyses were conducted in 188 DM-TB patients out of 901 enrolled in the Starting Anti-TB Treatment (St-ATT) cohort, with a median baseline glycosylated hemoglobin (HbA1c) of 8.2% (range 4.5-13.3%). Previous versus new DM diagnosis was associated with higher mean HbA1c (worse glycemic control) during treatment, with a smaller effect amongst those with central obesity (coefficient 0.80, 95% confidence interval [CI] 0.26, 1.57, P = 0.043) than amongst those without central obesity (coefficient 3.48, 95% CI 2.16, 4.80, P<0.001). In those with a new DM diagnosis, central obesity was associated with higher blood glucose (coefficient 1.62, 95% CI 0.72, 2.53, P = 0.009). Of 177 participants with ≥2 HbA1c results, 40% had uncontrolled glycemia (≥2 HbA1c results ≥8%). Of 165 participants with ≥3 HbA1c results, 29.9% had consistently-controlled glycemia, 15.3% had initially-uncontrolled glycemia, and 18.6% had consistently-uncontrolled glycemia. Previous versus new DM diagnosis and glucose-lowering medication use versus no use were associated with having uncontrolled versus controlled glycemia (adjusted odds ratio [aOR] 2.50 95%CI 1.61, 6.05, P = 0.042; aOR 4.78 95% CI 1.61,14.23, P<0.001) and more likely to have consistently-uncontrolled versus consistently-controlled glycemia (adjusted relative risk ratio [aRRR] 5.14 95% CI 1.37, 19.20, P = 0.015; aRRR 10.24 95% CI 0.07, 0.95, P = 0.003). Relapse cases of TB were less likely than new cases to have uncontrolled (aOR 0.20 95%CI 0.06, 0.63, P = 0.031) or consistently-uncontrolled (aRRR 0.25 95%CI 0.07, 0.95, P = 0.042) versus controlled glycemia. Those with long-term DM, suggested by previous diagnosis, glucose-lowering medication use and possibly central obesity, may require additional support to manage blood glucose during TB treatment.